Law and risk management in dental practice - Pollack, Burton R (Quintessence Pub. Co, 2002)
State Univ. of New York at Stony Brook. Topics include an introduction to the judicial system in the U.S., regulating dental practice, contract law, malpractice vs. negligence or breach of contract, statute of limitations and statute of repose, standards of care, vicarious liability, taking the history, patient records, risk management, and more. Softcover. DNLM: Dentistry.
Keywords: právo, zákonodárství; Risk Management; právní vědy; řízení rizik; Dentistry; Legislation, Dental; Spojené státy americké; zubní lékařství; United States; Jurisprudence; zákonodárství stomatologické; Medical Errors; chybná zdravotní péče